Lactobacillus casei Shirota Supplementation Does Not Restore Gut Microbiota Composition and Gut Barrier in Metabolic Syndrome: A Randomized Pilot Study. - Vanessa Stadlbauer; Bettina Leber; Sandra Lemesch; Slave Trajanoski; Mina Bashir; Angela Horvath; Monika Tawdrous; Tatjana Stojakovic; Günter Fauler; Peter Fickert; Christoph Högenauer; Ingeborg Klymiuk; et al. (PLoS ONE)
Unlabelled Metabolic syndrome is associated with disturbances in gut microbiota composition. We aimed to investigate the effect of Lactobacillus casei Shirota (LcS) on gut microbiota composition, gut barrier integrity, intestinal inflammation and serum bile acid profile in metabolic syndrome. In a single-centre, prospective, randomised controlled pilot study, 28 subjects with metabolic syndrome received either LcS for 12 weeks (n = 13) or no LcS (n = 15). Data were compared to healthy controls (n = 16). Gut microbiota composition was characterised from stool using 454 pyrosequencing of 16S rRNA genes. Serum bile acids were quantified by tandem mass spectrometry. Zonulin and calprotectin were measured in serum and stool by ELISA. Bacteroidetes/Firmicutes ratio was significantly higher in healthy controls compared to metabolic syndrome but was not influenced by LcS. LcS supplementation led to enrichment of Parabacteroides. Zonulin and calprotectin were increased in metabolic syndrome stool samples but not influenced by LcS supplementation. Serum bile acids were similar to controls and not influenced by LcS supplementation. Metabolic syndrome is associated with a higher Bacteroidetes/Firmicutes ratio and gut barrier dysfunction but LcS was not able to change this. LcS administration was associated with subtle microbiota changes at genus level. Trial registration ClinicalTrials.gov NCT01182844.